Undergraduate Students’ Self-Esteem and Motivation in Relation to Their English-Speaking Proficiency - Islamiah, Neneng; Hasbi, Muhamad (IJLHE: International Journal of Language, Humanities, and Education, 2024)
This study aimed to investigate whether the combination of students’ self-esteem and students’ motivation significantly explains their English-speaking proficiency, both separately and simultaneously. For this purpose, 38 students were selected among the undergraduate students of the Islamic Study Faculty, University of Muhammadiyah Prof. Dr. Hamka, Indonesia. A quantitative analysis was applied. To measure the students’ self-esteem and motivation, modified questionnaires were used, while their English-speaking proficiency was evaluated by two raters. The result showed a significant influence of the combination of the two variables on the dependent variable; English speaking proficiency. It indicated from the calculation by using SPSS version 17.00 which showed that the value of F-observed 11.463 is more than F-critical (3.27). The multiple correlation jointly between X1 and X2 and Y (Ry12) by 0.629 is significant. Moreover, the R-squared value of 0.396 can be interpreted that self-esteem and motivation together account for 39.6% of the variation in students’ English-speaking proficiency.